It's not fair! - Harper, Anita; McQuillan, Mary (New York : Holiday House, 2007)
A girl cat, resenting the preferential treatment enjoyed by her new baby brother, finds that she does get to do some things he cannot.
First published: Great Britain : Piccadilly Press, 1986.
Booklist.
Kirkus Review.
1.6
K-3
Keywords: Brothers and sisters -- Juvenile fiction; Cats -- Juvenile fiction; Infants -- Juvenile fiction; Babies -- Fiction; Brothers and sisters -- Fiction; Cats -- Fiction; Cats -- Fiction; Infants -- Fiction; Siblings -- Fiction; Picture books for children